Investigating the effect of a hotel's physical environment on customers' pleasure, satisfaction, loyalty and behavioural intentions: A conceptual framework - Suwanamas, Chayuth; Trimetsoontorn, Jirasek; Fongsuwan, Wanno (My University, 2015)
Customer experience is important for service providers in the hospitality and tourism industry. Research on customer experience broadly focuses on customer cognitions as an effect of customers' experiences and customers' experiences developed with the delivery of quality services. However, there is a lack of research considering a holistic view of customer experience considering emotions as a central element. Therefore, this paper aims to propose a framework to assess the influence of the physical environment on customers' pleasure, satisfaction, loyalty, and behavioural intentions. This framework will focus on atmospheric experiences of the visitors that affect their feelings and emotions at a luxury hotel and is based on Mehrabian and Russell's (1974) Stimulus Organism Response framework. The model is proposed to be tested across the hospitality and tourism industry by adopting a questionnaire based on literature review. Suggestions for managers and scholars are also given on implementing the core concepts of the model.
Keywords: Behavioural intentions; Customer satisfaction; Loyalty; Physical environment; Pleasure